2020
DOI: 10.1371/journal.pone.0240789
|View full text |Cite
|
Sign up to set email alerts
|

Intravaginal poly-(D, L-lactic-co-glycolic acid)-(polyethylene glycol) drug-delivery nanoparticles induce pro-inflammatory responses with Candida albicans infection in a mouse model

Abstract: In a recent study, using an in vitro model to study intravaginal nanoparticle exposure during yeast infections, we demonstrated that C . albicans exposure suppressed apoptotic gene expression and induced oxidative stress and pyroptosis in vaginal epithelial cells. The mucous-penetrating drug delivery nanoparticles made from poly-(D, L-lactic- co -glycolic acid)-(polyethylene glycol) induced cytotoxicity by activating apoptosis, endoplasmic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The results indicated that the mRNA expression of inflammatory factors was regulated by CuNPs and CuCl 2 exposure ( Figure 9 ). Proinflammatory cytokines like IL-1β, IL-6, and TNF-α are commonly assessed to estimate the immunotoxicity of nanomaterials [ 57 ]. Changes in the mRNA expression of these cytokines in the present study provided evidence of immunotoxicity associated with CuNPs and CuCl 2 exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the mRNA expression of inflammatory factors was regulated by CuNPs and CuCl 2 exposure ( Figure 9 ). Proinflammatory cytokines like IL-1β, IL-6, and TNF-α are commonly assessed to estimate the immunotoxicity of nanomaterials [ 57 ]. Changes in the mRNA expression of these cytokines in the present study provided evidence of immunotoxicity associated with CuNPs and CuCl 2 exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Nanodimensional materials, such as metallic NPs, metal-oxide NPs, lipid-based NPs, and polymeric NPs, have attracted considerable interest in recent years for fabricating delivery vehicles. Specifically, the variety and versatility of nanomaterials have been extensively explored by researchers for creating innovative therapeutic formulations that can be administrated on different routes, including oral [2,141,142], ocular [82,83,143], intranasal [125,129,130], intratracheal [55,144], intravaginal [145,146], intravesical [147,148], and transdermal [149,150] routes. Compared to free drugs, NP-loaded antimicrobial agents can be administered in so many ways due to their increased safety, reduced systemic adverse effects, enhanced solubility, and improved bioavailability.…”
Section: Discussionmentioning
confidence: 99%